2009
DOI: 10.1126/scisignal.290re7
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Redox Signaling by Electrophile-Protein Reactions

Abstract: Over the last 50 years, the posttranslational modification (PTM) of proteins has emerged as a central mechanism for cells to regulate metabolism, growth, differentiation, cell-cell interactions, and immune responses. By influencing protein structure and function, PTM leads to a multiplication of proteome diversity. Redox-dependent PTMs, mediated by environmental and endogenously generated reactive species, induce cell signaling responses and can have toxic effects in organisms. PTMs induced by the electrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
206
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 148 publications
(132 reference statements)
0
206
0
Order By: Relevance
“…The thiol of cysteine is one such target that can be oxidized by the ROS, 40 and lipid peroxidation products can also give rise to thiol oxidized products. 41 In the present study, it was found that nanoparticles with no or low concentration of dopants were causing more oxidation of the protein thiols compared to those with higher dopant concentration, that is, DNP2 and DNP3. DNP4 was responsible for the highest quantity of thiol oxidation products (102 nM) while DNP2 and DNP3 were producing ,40 nM (Figure 9).…”
Section: Protein Thiolsmentioning
confidence: 73%
“…The thiol of cysteine is one such target that can be oxidized by the ROS, 40 and lipid peroxidation products can also give rise to thiol oxidized products. 41 In the present study, it was found that nanoparticles with no or low concentration of dopants were causing more oxidation of the protein thiols compared to those with higher dopant concentration, that is, DNP2 and DNP3. DNP4 was responsible for the highest quantity of thiol oxidation products (102 nM) while DNP2 and DNP3 were producing ,40 nM (Figure 9).…”
Section: Protein Thiolsmentioning
confidence: 73%
“…Our understanding of the role of ROS in normal physiological signaling is evolving rapidly (3,33,36,37). The present studies define key roles for endogenous H 2 O 2 in cardiac myocytes that modulate Ang-II signaling pathways controlling eNOS activation and myocyte contractility.…”
Section: Resultsmentioning
confidence: 88%
“…However, not all effects of ROS are deleterious. Endogenously generated ROS have been implicated in posttranslational protein modifications that subserve critical roles in cellular signaling (3). Hydrogen peroxide (H 2 O 2 ) is one such ROS that has recently been identified as a key physiological signaling molecule in many cell types (4,5).…”
mentioning
confidence: 99%
“…Urinary Kelch-like ECH-associated protein 1 (Keap1) regulator of nuclear factor (erythroid-derived-2)-like 2 (Nrf2), heat shock factor-1 (HSF-1), peroxisome proliferator-activated receptor-␥ (PPAR ␥ ), and histone deacetylases (HDAC) ( 7 ). These transcriptional regulatory proteins contribute to the control of the expression of hundreds of genes that include cytokines, antioxidant enzymes, heat shock response proteins, and enzymes of intermediary metabolism ( 4,5,(8)(9)(10)(11)(12)(13)(14).…”
Section: Lipid Extraction From Urinementioning
confidence: 99%